A Randomized Phase 1 Pharmacokinetic Study Comparing the Potential Biosimilar LRG201902 With Liraglutide (Victoza®) in Healthy Male Subjects - Mai, Gang; Fan, Lianlian; Li, Mupeng; Zhang, Peiwen; Gan, Chunyan; Huang, Qian; Shentu, Jianzhong (Frontiers in Pharmacology, 2021)
Objective: Pharmacokinetic (PK) similarity between biosimilar candidate LRG201902 and European Union-sourced liraglutide reference product (Victoza®) was evaluated. Safety and immunogenicity were also assessed. Methods: This single-dose, randomized, open-label, 2-period crossover study (CTR20192342) was conducted in thirty-eight healthy adult male subjects. Volunteers were randomized 1:1 at the beginning to receive a single 0.6 mg dose of Victoza® or LRG201902 by subcutaneous injection during the first period. Following 8 days washout period, all subjects received the alternate formulation during the second period. Blood samples were collected up to 72 h after administration. The primary pharmacokinetic endpoints were AUC0–t, AUC0–∞, and Cmax. Pharmacokinetic similarity was achieved if 90% confidence intervals (CIs) of the geometric mean ratios (GMRs) of AUC0-t, AUC0–∞, and Cmax were within the range of 80–125%. Other pharmacokinetic parameters including Tmax, t½, and λz were also measured. Safety profile and immunogenicity data were collected from each subject. Results: Cmax, AUC0–t, and AUC0–∞ were similar between the two groups. GMRs of Cmax, AUC0–t, and AUC0–∞ were 113.50%, 107.21%, and 106.97% between LRG201902 and Victoza® respectively. The 90% CIs for the GMRs of Cmax, AUC0-t, and AUC0–∞ were all within the PK equivalence criteria. Mean serum concentration-time profiles, secondary pharmacokinetic parameters (Tmax, t½, and λz) were comparable between groups. Treatment-related adverse events were reported by 27.8% and 23.7% subjects in the LRG201902 and Victoza® arms, respectively. All post-dose samples were detected negative for anti-drug antibodies. Conclusion: This study demonstrates pharmacokinetic similarity of LRG201902 to Victoza® in healthy subjects. The safety and immunogenicity profiles were similar for the two products.